Studi Korelasional antara Minat Pasien dan Sarana Prasarana Terkait Kepuasan Pasien Rawat Inap di Rumah Sakit TNI AU Sam Ratulangi Manado - Emmanuela R. Molenaar; Herman Karamoy; Freddy Wagey; Welong S. Surya (Universitas Sam Ratulangi, 2023)
Abstract: As a health institution, hospitals are required to understand the needs of patients based on quality service that could affect the patients’ satisfaction towards the attitudes of medical and non-medical personnels, the facilities and infrastructure provided, and the environment that makes the patients feel comfortable and safe. This study aimed to determine the relationships between patients’ interest and infrastructure with patients’ satisfaction at Rumah Sakit TNI AU Sam Ratulangi Manado. This was a quantitative study. Samples were 67 inpatients obtained by using the quota sampling technique. Data were analyzed with the chi-square test. The results showed that based on the patients’ satisfaction, 58.2% of respondents were satisfied and 41.8% were dissatis-fied. Based on patients’ interest, 50.7% were interested and 49.3% were not interested. Based on facilities and infrastructure, 50.7% were good and 49.3% were not good. The results of the chi-square test confirmed that there was a relationship between patients’ interest and patients’ satisfaction (p=0.000), and there was a relationship between facilities and infrastructure with patients’ satisfaction (p=0.000). In conclusion, there are positive relationships between the patients’ interest as well as facilities and infrastructure with the patients’ satisfaction at Rumah Sakit TNI AU Sam Ratulangi Manado. Keywords: patients’ satisfaction; patients’ interest; facilities and infrastructure Abstrak: Rumah Sakit sebagai institusi kesehatan harus memahami kebutuhan pasien dalam hal kualitas pelayanan yang dapat memengaruhi kepuasan pasien terkait kepuasan terhadap sikap tenaga medis maupun non medis, sarana dan prasarana yang disediakan, serta lingkungan yang membuat pasien merasa nyaman dan aman. Penelitian ini bertujuan untuk mengetahui hubungan antara minat pasien dan sarana prasarana dengan kepuasan pasien rawat inap di Rumah Sakit TNI AU Sam Ratulangi Manado. Jenis penelitian ialah kuantitatif. Sampel penelitian sebanyak 67 responden diperoleh dengan menggunakan teknik quota sampling. Analisis statistik menggunakan uji chi square. Hasil penelitian mendapatkan variabel kepuasan pasien yang puas sebesar 58,2% dan tidak puas 41,8%. Variabel minat pasien yang minat sebesar 50,7% dan tidak minat 49,3%. Variabel sarana prasarana yang baik sebesar 50,7% dan kurang baik 49,3%. Hasil uji chi-square menegaskan adanya hubungan antara minat pasien dengan kepuasan pasien (p=0,000), dan adanya hubungan antara sarana prasarana dengan kepuasan pasien (p=0,000). Simpulan penelitian ini terdapat hubungan bermakna antara minat pasien dan sarana prasarana dengan kepuasan pasien di Rumah Sakit TNI AU Sam Ratulangi Manado. Kata kunci: kepuasan pasien; minat pasien; sarana prasarana